The Influence of Financial Knowledge and Financial Attitudes on Financial Management Behavior on UMKM Actors in Lahomi Sub-District - Dimensi Daeli; Perlindungan F. Hulu; Nanny A. Bu’ulolo; Maria Magdalena Bate’e (Golden Ratio of Data in Summary, 2024)
This research aims to determine the influence of financial knowledge and financial attitudes towards financial management behavior among MSMEs in Lahomi sub-district. This research is included in associative research. This result of the research shows that (1) there is a positive and significant influence of financial knowledge on financial management behavior among MSMEs in Lahomi District (2) there is a positive and significant influence of financial attitudes on financial management behavior among MSMs in Lahomi District (3) there is a positive and not significant influence on the financial management behavior of MSMEs in Lahomi District.